CAE - PROCESS AND NETWORK : A methodology for continuous product validation process based on network of various digital simulation methods - Syal, Gagan (Reihe Informationsmanagement im Engineering Karlsruhe / Hrsg.: Karlsruher Institut für Technologie, Institut für Informationsmanagement im Ingenieurwesen (IMI), 2013)
CAE ProNet methodology is to develop CAE network considering interdependencies among digital validations. Utilizing CAE network and considering industrial requirements, an algorithm is applied to execute a product, vehicle development phase, and load case priority oriented CAE process. Major advantage of this research work is to improve quality of simulation results, reducing time-to-market and decreasing dependencies on hardware prototype.